Improving data reliability to support marine pollution assessment according to MSFD Descriptor 8 in the European Seas: the contribution of EMODnet Chemistry - French, Megan Anne; Lipizer, Marina (Frontiers in Marine Science, 2023)
According to the Marine Strategy Framework Directive (MSFD, 2008/56/EC), member states of the European Union (EU) had to develop a common approach in environmental monitoring and assessment. Regarding marine pollution assessments, high heterogeneities remain regarding sampling protocols, analytical methods, and quality assurance (QA) and quality control (QC) procedures. Further, data availability for Descriptor 8 (contaminants) was very fragmented in the first cycle of the MSFD. As one of the major EU spatial data infrastructures for providing access to marine data, EMODnet Chemistry has endeavoured to overcome data fragmentation and increase data 'FAIRness' (findable, accessible, interoperable, and reusable). Aiming to improve the reliability of marine contaminant data for assessment purposes under the MSFD, detailed QA/QC information was collected using a questionnaire based on the requirements of the European Environment Agency, International Council for the Exploration of the Sea, United Nations Environment Program-Mediterranean Action Plan, and NORMAN Network. The questionnaire was distributed to institutions in 26 countries participating in EMODnet Chemistry. Information was received from 18 countries on ~90% of the substances included in EU legislation on priority substances. The results indicate an overall good level of laboratory proficiency; however, heterogeneities were observed in sampling protocols (especially for biota) and analytical methods (e.g. for metals), suggesting the potential for increased harmonisation. While laboratory proficiency and equipment depend on institutional resources that may differ among countries, it is fundamental to share detailed QA/QC information associated with data to improve data reliability and re-usability, and to support marine pollution assessment. Enriching data with required metadata and detailed QA/QC is part of the data curation process, which is still an overlooked aspect of the overall scientific research process and is crucial to support a reliable assessment of marine pollution, and ultimately better management of the marine environment.